Pentingnya Entrepreneurial Education, Attitude towards Entrepreneurship, dan Creativity terhadap Entrepreneurial Intention - Allison Eloise Charlene; Sarwo Edy Handoyo (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
Penelitian ini bertujuan untuk menganalisis pengaruh pendidikan kewirausahaan, sikap terhadap kewirausahaan, dan kreativitas terhadap niat berwirausaha mahasiswa universitas swasta di Jakarta Barat. Dalam penelitian ini, teknik pengambilan sampel yang digunakan adalah non-probability sampling dengan metode purposive sampling, melibatkan 189 responden yang merupakan mahasiswa universitas swasta di Jakarta Barat. Data dikumpulkan melalui kuesioner daring menggunakan Google Form dan dianalisis dengan metode Partial Least Square Structural Equation Modeling (PLS-SEM) menggunakan aplikasi SmartPLS 4.0. Hasil penelitian menunjukkan bahwa pendidikan kewirausahaan, sikap terhadap kewirausahaan, dan kreativitas memiliki pengaruh positif dan signifikan terhadap niat berwirausaha mahasiswa. Pendidikan kewirausahaan berperan penting dalam membangun pengetahuan dan keterampilan yang relevan untuk mendukung niat berwirausaha. Sikap terhadap kewirausahaan memperkuat keyakinan mahasiswa dalam menghadapi tantangan bisnis, sedangkan kreativitas mendorong inovasi dan ide-ide baru dalam proses kewirausahaan. Penelitian ini memberikan kontribusi teoretis dalam memahami faktor-faktor yang memengaruhi niat berwirausaha. Secara praktis, hasil ini dapat digunakan oleh universitas untuk merancang program pendidikan kewirausahaan yang lebih efektif, serta memberikan panduan bagi mahasiswa untuk mempersiapkan diri dalam menciptakan usaha yang inovatif. A person's entrepreneurial intentions greatly influence the economy in Indonesia. There are several data that show the economic situation in Indonesia, such as Indonesian people's views on business, the number of Indonesian entrepreneurs is decreasing, the employment situation in West Jakarta is decreasing, and the economic growth situation in West Jakarta is decreasing. This research aims to analyze the influence of entrepreneurship education, attitudes towards entrepreneurship, and creativity on the entrepreneurial intentions of private university students in West Jakarta. In this research, the sampling technique used was non-probability sampling with a purposive sampling method, involving 189 respondents who were private university students in West Jakarta. Data was collected through an online questionnaire using Google Form and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method using the SmartPLS 4.0 application. The research results show that entrepreneurship education, attitudes towards entrepreneurship, and creativity have a positive and significant influence on students' entrepreneurial intentions. Entrepreneurship education plays an important role in building relevant knowledge and skills to support entrepreneurial intentions. Attitudes towards entrepreneurship strengthen students' confidence in facing business challenges, while creativity encourages innovation and new ideas in the entrepreneurial process. This research provides theoretical contributions in understanding the factors that influence entrepreneurial intentions. Practically, these results can be used by universities to design more effective entrepreneurship education programs, as well as provide guidance for students to prepare themselves to create innovative businesses.